VIRTUAL MODELING AND MONITORING OF AIRCRAFT PARTS - Ainakulov Ж.Ж.; Zuev Д.В.; Seidakhmetov Б.К.; Fedorov И.О.; Koshekov К.Т. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
This work considers the relevance of the use of virtual reality technology, and specifically virtual prototyping, in different areas of application. The main tasks, analyzed in the virtual collection of details solved with the help of a set of software and hardware for visualization. The use of virtual reality technology in the educational process allows you to increase the success and at the same time reduce the amount of errors and losses. The introduction of training programs through the use of virtual reality technology allows to improve the quality and reduce the period of training, which will be saved on the savings of funds spent on the training of specialists. Training programs can be used in the process of training specialists. As a result of the implementation of this stage of the study, the qualitative and quantitative requirements for the hardware-software complex of interactive educational programs are determined.